Islamic Religion's Oral Dakwah in Socialised Halal Product Certification in The District of Kejaksan, Cirebon City - Falah, Achmad; Askolani, Muhammad; Sanusi, Taofeeq Olamilekan (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
Verbal da'wah (da'wah bil oral) is a verbal communication method used by Islamic religious counselors to convey Islamic teachings, including the socialization of halal product certification. In Kejaksan District, Cirebon City, public awareness and business actors' compliance with halal certification still needs improvement. Religious counselors play a crucial role in providing an understanding of the urgency of consuming halal products in accordance with Islamic teachings and applicable regulations. Through a persuasive communication approach, logical arguments, emotional appeals, and ethical considerations are the primary strategies in verbal da'wah to increase public awareness and adherence to halal products. This study aims to describe the strategies employed by Islamic religious counselors in socializing halal certification, focusing on three aspects: (1) the presentation of logical arguments based on the Qur'an, hadith, and relevant regulations; (2) the emotional approach through inspirational stories and real-life experiences to build a connection with the community; and (3) ethical preaching that emphasizes politeness and persuasive methods to ensure message acceptance without resistance. This r esearch employs a qualitative approach with a descriptive method and a case study design. Data collection was conducted through observation, interviews, and documentation. The findings indicate that religious counselors present logical arguments regarding the obligation of consuming halal products and their relationship to health and blessings. The emotional approach is implemented through inspirational narratives that foster empathy within the community. Meanwhile, ethical and persuasive preaching, as recommended in Surah An-Nahl: 125, ensures that the message is well received. This study recommends further exploration of the effectiveness of verbal da'wah in socializing halal certification through digital platforms, such as social media and Islamic educational applications. A comparative study in different regions is also suggested to assess the effectiveness of da'wah methods in diverse social and cultural contexts. The findings are expected to contribute to innovations in da'wah and expand the reach of halal certification socialization.